Determinação de glifosato e ampa em água por injeção direta da amostra em cromatografia iônica capilar e LC-MS/MS - Matos, Fábio da Silva de (2014)
Glyphosate [N-(phosphonomethyl) glycine] is the most widely used pesticide in the world for controlling weeds in agriculture. High amounts of this herbicide and its major metabolite, aminomethylphosphonic acid (AMPA), have been found in water due to intensive use. The Ministry of Health 2914 establishes a maximum value allowed for the sum of glyphosate and AMPA at 0.5 mg L-1. The most comum method to determine these compounds requires a derivatization step for fluorescence detection. Thus, this study aimed to develop two simple and rapid methods for the direct determination of glyphosate and AMPA in water without treatment or sample derivatization steps, by capillary ion chromatography (Capillary IC) and liquid chromatography tandem mass spectrometry (LC-MS/MS). The Capillary IC method employed a capillary IonPac AS19 column (250 x 0.4 mm, 7.5 μm), a gradient elution with KOH a conductivity detector. The LC-MS/MS method used a Pursuit XRS C18 column (150 x 2 mm ID, 5 μm), an aqueous solution of ammonium hydroxide 0.01% (v/v) as mobile phase and a triple-quadrupole MS detector, operating in a selected reaction monitoring (SRM) mode. The method validation was performed by recovery experiments, evaluating accuracy, precision, linearity, limits of detection (LOD) and of quantification (LOQ). The analytical curves for glyphosate and AMPA obtained for the concentration levels 25, 50, 100, 250 and 500 μg L-1 by Capillary IC and LC-MS/MS showed r2 >0.99 for both compounds. For spiked levels of 25, 50, 250 and 500 μg L-1 recoveries were between 70 -113%, with RSD <10% for Capillary IC and 79-105%, with RSD <14% for LC-MS/MS. The method limits of detection for both glyphosate and AMPA was 8 μg L-1 and of quantification was 25 μg L-1, in both chromatographic techniques. Both methods showed good selectivity and sensitivity. Determination by direct injection of the sample, using capillary IC or LC-MS/MS proved to be efficient, simple and cost-effective tools for analysis, making it possible to monitor at levels below the maximum allowed limits for drinking water.